PUBLIC TRANSPORT INFORMATION SYSTEM IN THE BOJONGGAMBIR SUB-DISTRICT AREAIOT BASED - Lesmana, Hilman; Haryanto, S.T,M.Kom, Dadang (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
With the rapid development of science and technology, especially in the modern era like now, technological developments are influenced by the high demand for technology to support daily activities. For modern society, as it is now, the role of technology and information systems that are accurate, effective and efficient to facilitate carrying out activities will be very much needed both in business, social or educational activities. In social activities, it is hoped that technology can help speed up the community in obtaining precise and accurate information so that it makes it easier for people to carry out their daily activities smoothly. Information is very important for a good social life so that there will be no more disinformation that can harm society. As an example here the author takes the case of disinformation that is often experienced by public transport users in the Bojonggambir District area, there are many public transport users experiencing disinformation because of the limited information they get when they want to use public transportation either as passengers or as a means of sending goods. . Losses due to disinformation above can be overcome by utilizing information technology such as a microcontroller by using the NodeMCU ESP8266 as a real-time information link device by utilizing the internet network as an information link.   The results of this study indicate that the existence of technology will greatly assist in social sustainability so that the problems that exist in people's lives, especially in social life, the authors hope that the existence of a public transport information system in the Bojonggambir sub-district based on IoT (Internet of Things) will be very helpful in carrying out community activities, especially those who use public transportation in carrying out their daily activities